Prevalence Impact of Misuse of Montelukast in Children: A Hospital-Based Observational Study (Journal of Chittagong Medical College Teachers' Association, 2025)
Background: Montelukast, a leukotriene receptor antagonist, is widely prescribed for asthma and allergic rhinitis in children. However, its misuse has raised concerns regarding adverse effects and long-term outcomes. This study was conducted in a low-resource setting in Bangladesh to evaluate the impact of montelukast misuse in children aged 6 months to 10 years. To assess the prevalence of montelukast misuse, identify associated Adverse Drug Reactions (ADRs), and evaluate long-term complications in children.Materials and methods: A prospective, hospital-based  observational study was conducted at BGC Trust Medical  College Hospital from January 2021 to January 2025. A total of 500 children were enrolled, and data were collected from indoor and outdoor patient departments using a structured questionnaire . Misuse was defined as off-label use, incorrect dosing or prolonged use without indication. Outcomes included ADRs, treatment efficacy and long-term complications. Statistical analysis was performed using Chi-square and ANOVA tests, with a significance threshold of p < 0.05.Results: Among the 500 children, 40% (n=200) were found to have misused montelukast, with incorrect dosing being the most common form (25%, p < 0.001). ADRs were reported in 35% (n=175) of cases, including neuropsychiatric symptoms (12%, p < 0.001), gastrointestinal disturbances (10%, p < 0.002) and respiratory complications (8%, p < 0.003). Long-term complications were observed in 15% (n=75) with growth retardation (6%, p < 0.001) and behavioral changes such as aggression, anxiety, and sleep disturbances (9%, p < 0.002). The prevalence of misuse increased from 30% in 2021 to 45% in 2025 (p < 0.001).Conclusion: Misuse of montelukast in children is associated with significant adverse effects and long-term complications. Strict adherence to prescribing guidelines, parental education and healthcare provider training are essential to minimize risks. These findings underscore the need for stricter regulatory oversight and targeted educational interventions. JCMCTA 2025 ; 36 (1) : 107-113